Relation between foot arch index and ankle strength in elite gymnasts: a preliminary study - Aydog, S. T.; Ozcakar, L.; Tetik, O.; Demirel, H. A.; Hascelik, Z.; Doral, M. N. (British Journal of Sports Medicine, 2005)
Background: Gymnasts usually start intensive training from early childhood. The impact of such strenuous training on the musculoskeletal system is not clear.